MIS Distal Metatarsal Metaphyseal Osteotomy in the treatment of metatarsalgia: MOXFQ patient reported outcomes. (June 2020) - McMurrich, W.; Peters, A.; Ellis, M.; Shalaby, H.; Baer, G.; MacDonald, D.; McKinley, J.C.
Abstract: Introduction: The aim of this paper is to present validated patient reported outcomes for MIS Distal Metatarsal Metaphyseal Osteotomy (DMMO) in the treatment of metatarsalgia. The study aims to evaluate the DMMO procedure, report patient satisfaction with the operated foot and report any complications of this procedure. Patients and methods: Between 2014 and 2016, patients who had failed conservative treatment for metatarsalgia were identified in the orthopaedic outpatient clinic. Twenty four consecutive patients requiring DMMO plus/minus toe straightening were prospectively studied. Patients requiring additional procedures at the time of surgery were excluded. Patients completed the validated Manchester-Oxford Foot Questionnaire (MOXFQ) three weeks pre-operatively and 1 year postoperatively. The MOXFQ results were analysed using Paired t-tests. A supplementary question was asked regarding patient satisfaction with the operated foot. Results: There were 20 women and 4 men with a mean age of 64 years (sd 8.6). Statistically significant differences were found between the pre and postoperative MOXFQ. The postoperative MOXFQ score demonstrated a poorer result for two patients, no change for two patients and improvement in 20 patients, with four of these patients recording the lowest possible score. There was a 29.5 point improvement in mean metric MOXFQ Index score. Seventy-nine percent (n = 19) of patients were satisfied or very satisfied with the operated foot. The average recoil of the metatarsal heads following DMMO was M2 4.01 mm, M3 4.55 mm, M4 4.16 mm. There was one delayed union and no non-unions. Further reported complications were a gastric bleed, pulmonary embolism (VTE), and one intra operative broken burr. Conclusion: Our study demonstrates a clinically important and statistically significant improvement in patient reported outcomes following DMMO, with 79% of patients satisfied or very satisfied with this procedure. The average recoil of the metatarsal heads following DMMO was M2 4.01 mm, M3 4.55 mm, M4 4.16 mm with one delayed union and no non-unions.